Evaluation of ice thermal energy storage (ITES) for commercial buildings in cities in Brazil. (February 2017) - Arcuri, Bruno; Spataru, Catalina; Barrett, Mark
Highlights: ITES can effectively shape peak demand in commercial buildings in Brazil. ITES must be considered in AC load management due to impacts on grid peak demand. ITES generated economic gains but also losses in commercial buildings in Brazil. Economic gains are dependent on the cooling load profile, ITES strategy and tariff. Tariffs could be designed to incentivise AC load management measures such as ITES. Abstract: High temperatures and the intensive use of air conditioning are considered the main drivers of the increase in Brazil's electricity demand in the summer, which has been causing major power cuts due to insufficient supply to meet peak demand. This paper analyses the techno-economic aspects of Ice Thermal Energy Storage (ITES) in Brazil, as a technology that can be used to shift building cooling load to off-peak time. ITES is assessed in five cities and five archetypes of commercial buildings, using two different operation strategies and two types of chillers, for new installations and retrofits. Results have shown that ITES can effectively shape peak demand in commercial buildings, generating economic gains for building owners but also losses in some cases. Although the climate plays an important role, the electricity tariffs vary significantly from city to city and this determined the economic feasibility of ITES. The technology's potential to shape demand in Brazil's commercial sector can encourage policy makers, regulators, grid operators and utilities in considering ITES as an option to reduce peak demand, increase security of supply and support the integration of intermittent renewable generation.